Micro-computed tomographic analysis of filling porosity of two different obturation techniques - Amal A Almohaimede; Marwa M Almutairi; Haya M Alyousef; Ebtissam M Almadi (Wolters Kluwer Medknow Publications, 2019)
Introduction: The ideal root filling material should have inert properties, good adhesive ability, and result in void-free obturation along the root canals. The aim of this in vitro study was to compare the quality of two root canal obturation techniques; cold lateral (CL) condensation and continuous wave (CW) condensation, through measuring the volume of gaps and voids by using micro-computed tomography (micro-CT). Materials and Methods: Forty-extracted teeth with single canal were instrumented with profile rotary files, and divided into two groups as follows: CL condensation (n = 20), and CW obturation (n = 20). The teeth in each obturation group were scanned twice using micro-CT scan. The resultant images were rendered in proprietary software (NRecon version 1.6.9.4) to obtain three-dimensional (3D) pre- and post-obturation records of each specimen. The 3D images were imported into CT Analyser version 1.17.7.2 for volume measurement of voids and gaps in the apical third at 1 mm, 3 mm, and 5 mm. The analysis of variance test was used to compare the mean volume of voids and gaps between the two obturation groups in each level in the apical third (1 mm, 3 mm, and 5 mm). Furthermore, it was used to compare the mean volume of voids and gaps between the three different levels apically in each obturation technique. Results: CW obturation technique had more voids volume at the three different apical levels (1 mm: 0.19 ± 0.16, 3 mm: 0.76 ± 0.81, and 5 mm: 1.36 ± 1.44) compared to CL condensation technique at the same three levels (1 mm: 0.14 ± 0.21, 3 mm: 0.46 ± 0.46, and 5 mm: 1.10 ± 0.93) with no statistical significant difference between them (P < 0.05). Conclusions: None of the root canals filled teeth were voids-free, and there was no statistically significant difference between the two obturation techniques regarding the gaps volume apically.